A (Dis)entangled History of Early Modern Cannibalism: Theory and Practice in Global History. (December 2022) - McManus, Stuart M.; Tworek, Michael T.
Abstract: This article offers a new approach to early modern global history, dubbed (dis)entangled history as a way to combine the conventional focus on the history of connections with a necessary appreciation of the elements of disconnection and disintegration. To exemplify this approach, it offers a case study related to the history of cannibalism as both a disputed anthropophagic practice and a cultural reference point across the early modern world. Through a rich multilingual and multimedia source base, we trace how the idea of Indigenous Tapuya endo-cannibalism in Brazil travelled across the Atlantic through Europe and Africa to East Asia. The idea of Tapuya cannibalism crossed some linguistic borders, stopped at others and interacted unevenly with long-standing Ottoman, Polish, West African, Islamic and Chinese ideas about 'cannibal countries', of which it was just one more example. This trajectory challenges the historiographical consensus that early modern ideas about cannibalism were centred on the Atlantic world. By tracing how one particular discourse did and did not travel around the globe, this article offers not just a theoretical statement, but a 'fleshed out' and concrete approach to writing about intermittent connectedness during the period 1500–1800.